Purchase Intention of Customers Toward Health Products in Melaka State - Marhaban, N.A.; Rahim, N.A.; Azmi, F.R.; Hamdan, N.; Musa, H. (International Journal of Human and Technology Interaction (IJHaTI), 2020)
Abstract - Currently, the number of companies offering health products is increasing over the years. This varied range of options available for customers has driven the researchers to dig out what the factors are that influence the intentions of purchasing by customers. The importance of this research was to actually realize what are the factors that could impact the behavior of customers in deciding which product to be purchased or to be bought. The objectives of this research are to investigate the impact or relationship of customer knowledge, product performance, and health concern towards the purchase intention of consumers toward health products. In addition, the research is classified as a descriptive study to collect data by using a quantitative method. The researcher had distributed survey questionnaires to 201 respondents through online distribution after manual questionnaires have been answered by 20 respondents during the pilot test. Data gathered and analyzed by using SPSS software. The results obtained showed significant influences between customer experience, customer attitude, perceived values, perceived usefulness, and health background on purchase intention of consumers toward health products. However, perceived ease of use and health awareness failed to achieve a significant correlation with the intention of purchase by consumers. Based on the discussions made on findings, this research may be able to be explored deeper view through further research in the future and eventually contributing to the industry. Keywords - Health products, customer attitude, customer experiences, perceived values, perceived usefulness, health background, purchase intention towards health products